2016
DOI: 10.1155/2016/4365217
|View full text |Cite
|
Sign up to set email alerts
|

Serous Cystadenocarcinoma Arising in Presumed Vitelline Duct Remnant: A Case Report and Implications in the Management of Cancer of Unknown Primary

Abstract: Background. Malignant neoplasms arising in Meckel's diverticulum, a vitelline duct remnant, are rare yet well-documented. Case Presentation. A 53-year-old previously healthy female presented with an enlarging midline abdominal wall mass. A computed tomography scan revealed a mass involving the linea alba, bilateral rectus abdominis, and subcutaneous fat. Extensive clinical workup failed to demonstrate other lesions, except local and paratracheal/hilar lymphadenopathy. Histopathologic examination of the resecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A literature review revealed no reports of MD adenocarcinoma with an umbilical side of VDR or a huge cystic lesions; our case is therefore considered to be the first one. As for the E type, which occurs in the abdominal wall of the umbilicus, only two cases have been reported [ 8 , 9 ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…A literature review revealed no reports of MD adenocarcinoma with an umbilical side of VDR or a huge cystic lesions; our case is therefore considered to be the first one. As for the E type, which occurs in the abdominal wall of the umbilicus, only two cases have been reported [ 8 , 9 ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%